The Use of Interaction-Based Activities to Improve Reading Comprehension - Dahlina, Ulinuha; Lailah, Sitrotul (JEDLISH : Journal Of Education and English Language Teaching, 2022)
This research study was aimed at improving students’ reading comprehension by using interaction-based activities of grade VIII B students at SMPN 1 Kramatwatu in the academic year of 2020/2021. The actions were conducted based on the curriculum and in line with the course grid and lesson plan developed before conducting the interaction0based activities. This research was action research. It consisted of two cycles, which was conducted for three meetings in the first cycle and second cycle. The subjects of this research study were 36 students of grade VIII B at SMPN 1 Kramatwatu. The data were qualitative and quantitative. The qualitative data were collected through observation, interviews with the students, the English teacher and the research collaborator, and documentation the teaching and learning process. The data were in the forms of field notes, interview transcripts, vignettes, and photographs. While the quantitative data were obtained from tests (pre-test and post-test). The validity of the data was obtained by applying democratic validity, outcome validity, process validity, catalytic validity, and dialogic validity. Time triangulation, theoretical triangulation, and investigator triangulation were also applied to check the trustworthiness of the data. The interaction-based activities were used in each stage to improve the interaction between the students and the teacher. The actions conducting during this research study involved implementing the interaction-based activities, training the students to use reading techniques and strategies, teaching grammatical points, using power point presentations, pictures, and handout, and motivating the students through stories and giving rewards. The research study outcomes show that the students’ reading comprehension improved through the interaction-based activities. There were also improvements in their involvement, confidence and motivation. In terms of reading the texts, the students used some reading techniques and strategies, such as scanning, skimming, and guessing. In terms of students’ behavior, the students also improved their confidence to participate actively in the classroom. The students did not worry of making mistakes in using the English language. The students were active in the discussion activity and giving feedback to each other and helping each other in the classroom activities. The students were enthusiastically in learning reading. Moreover, the students could answer the comprehension tasks well. Furthermore, the students’ reading comprehension were measured quantitatively by comparing mean score of Cycle I and Cycle II. The result revealed that the students’ reading comprehension improved.